Technical success, procedural safety, and efficacy of the Silk Vista Baby in the treatment of cerebral aneurysms over a mid-to-long-term follow-up - Rodríguez-Fernández, Claudio; Ruiz-Garcia, Pedro; Garcia-Sanchez, Maria Jesús; Manrique-Zegarra, Martiel; Toledano-Illán, Carlos; Escartin, Jorge; Vences, Miguel Angel; Rubio, Luis Angel; Luttich, Alex; Pumar, José Manuel (Frontiers in Neurology, 2024)
Background Long-term follow-up of cerebral aneurysms treated with the Silk Vista Baby (SVB) flow diverter is lacking. This study aimed to assess the technical success, procedural safety, and efficacy of the SVB (Balt, Montmorency, France) for the treatment of intracranial aneurysms in small cerebral vessels over a mid-to long-term follow-up. Methods We retrospectively analyzed a prospectively maintained database of patients treated with the SVB between September 2018 and June 2021. Data regarding patient demographics, aneurysm characteristics, and technical procedures were also collected. Angiographic and clinical findings were recorded during the procedure and over a period of at least 12 months. Results Angiographic and clinical follow-up data were available for 50 patients/50 aneurysms. The procedural complication rate was 8%. At 12 months, the final results showed a technical success rate of 100%, the re rupture rate was 0%, neuromorbidity and mortality rates of 4 and 0%, respectively, and an almost complete occlusion rate of 94%. Conclusion Treatment of complex intracranial aneurysms with the SVB was safe and effective. Long-term results showed high rates of adequate and stable occlusions.